The Influence of Project Based Learning Model on Creative Thinking Skills and Physics Learning Outcomes - Nala Oktavia Wulandari; Sutrio; Aris Doyan; Satutik Rahayau (Jurnal Penelitian Pendidikan IPA, 2024)
This study examines the impact of the Project-Based Learning (PjBL) model on high school students' creative thinking skills and physics learning outcomes. Using a quasi-experimental design with a Nonequivalent Control Group, data were collected through pre-tests and post-tests from 71 students divided into experimental and control classes at SMAN 1 Gerung. The findings reveal that the PjBL model significantly enhances students' creative thinking skills, with the experimental class showing a higher improvement (from 42.58 to 76.29) compared to the control class (from 37.41 to 67.77). Additionally, the PjBL model effectively improves cognitive, affective, and psychomotor outcomes, as evidenced by higher post-test scores and improved engagement, collaboration, and responsibility among students in the experimental class. These results suggest that the PjBL model is an innovative and effective approach to fostering 21st-century skills such as creativity, problem-solving, and critical thinking while addressing the limitations of traditional, teacher-centered methods. This research contributes to the development of interactive and student-centered teaching strategies, particularly in physics education, and provides valuable insights for enhancing academic and life skills in students.